(untitled) (Research, Society and Development, 2022)
The objective of this research is to classify the potential environmental impacts resulting from tanneries and suggest environmental control measures for such impacts. The methodology used consisted of surveys and bibliographic studies, through readings of scientific articles, books, manuals (Manual de Impactos Ambientales do Banco do Nordeste), Reports and Environmental Impact Studies, with the purpose of collecting information necessary for the identification and classification of the environmental impacts resulting from the implementation of tanneries. It becomes evident that the significant environmental impacts, whether positive or negative, resulting from all activities carried out at all stages of a project of a given enterprise, must be studied, in order to assess the environmental feasibility for the implementation from the project. The planning phase does not present significant environmental impacts and that the significant environmental impacts are more observed in the implementation phase of the enterprise. The environmental factors: soil and water resources, as well as the biotic factors fauna and flora had a lot of significant negative impacts. Of the 38 impacts identified, 32 were considered significant, of these 29 were considered negative, 3 were considered positive and 6 were considered not significant.